GENDER DIFFERENCES IN LIPIDS AND LIPOPROTEIN (a) PROFILES IN HEALTHY INDIVIDUALS AND PATIENTS WITH TYPE 2 DIABETES MELLITUS - Habib, Syed Shahid; Aslam, Muhammad; Hameed, Waqas (Pakistan Journal of Physiology, 2005)
This study aimed to assess gender differences in blood lipids and lipoprotein(a) levels in healthy individuals and patients with type 2 diabetes mellitus. Methods: This study was carried out at Department of Physiology, Army Medical College, Rawalpindi, Pakistan Sixty four patients suffering from type 2 DM and forty one healthy individuals were studied. The subjects were divided into healthy females, healthy males, type 2 DM females and type 2 DM males group. Fasting blood samples were analyzed for lipoprotein(a) [Lp(a)], total cholesterol (TC), triglycerides (TG), low density lipoprotein cholesterol (LDL-C), high density lipoprotein cholesterol (HDL-C), glucose and glycosylated hemoglobin (HbA1c). Results: When the lipid profile of healthy females was compared with the lipid profile of healthy males it was observed that HDL-C levels were significantly higher in healthy females as compared to healthy males (p < 0.05) while serum triglycerides were significantly raised in healthy males as compared to healthy females(p < 0.05). Diabetic females had significantly higher levels of LDL-C, HDL-C , TG and Lp(a) levels as compared to healthy females (p < 0.01, p < 0.05, p < 0.05 and p < 0.05). Diabetic males had significantly higher levels of TC, LDL-C, HDL-C and Lp(a) levels than healthy males (p < 0.01, p < 0.05, p < 0.01, and p < 0.05). The difference in lipid and Lp(a) profile was non significant between diabetic females and diabetic males. Conclusions: There are gender differences in lipid profile in patients with type 2 diabetes mellitus and well as healthy individuals.